Identification of Cultural Values and Nation’s Character in Dalung Bojong Inscription of the Sultanate of Banten in Lampung - Kian Amboro; Kuswono Kuswono; Adi Setiawan (UIN Sumatera Utara Medan, 2021)
This study aims to identify the cultural values and character of the nation in the text of the Dalung Bojong Inscription of the Sultanate of Banten in Lampung. The content analysis (content) method with a descriptive qualitative approach was used in this study. The results indicated that the Dalung Bojong Inscription contained ten cultural values and national characters, including the following: 1) Tolerance; 2) Democratic; 3) Friendly/ Communicative; 4) Peaceful; 5) Discipline; 6) National Spirit; 7) Responsibility; 8) Patriotism; 9) Social Concerns; 10) Appreciating Achievements. It is concluded that the value of Discipline is the predominating value in the inscription text's 12 articles. It is demonstrated by the text of the Dalung Bojong Inscription, which contains a set of regulations aimed at controlling, regulating, and maintaining order in the Lampung people's political, economic, and social lives.